HOME INDUSTRY OF LEATHER CRAFTS IN MAGETAN REGENCY EAST JAVA REVIEWED FROM FUNCTIONAL THEORY - Hartutik Hartutik (Bajang Institute, 2021)
In Magetan Regency, East Java Province, there is a home industry of leather crafts, precisely at Jalan Sawo, Selosari Village. The leather crafts is a form of physical culture which is currently being developed and preserved. Operationally the production process is carried out there and marketing is also carried out outside the region. The production process involves employees from the local community while marketing is not only carried out in shops on Jalan Sawo, but also sent to various regions in Indonesia. The products produced are shoes, slippers, bags, wallets, belts, and jackets. This study aims to describe the leather crafts home industry in Magetan Regency when viewed from a functional theory. This study combines field research with library research. Data collection techniques are carried out through interviews, observation, and documentation. Meanwhile, data analysis used the interactive model of Milles and Huberman's. Based on the research results, it can be seen that there is a relationship between functional theory and the leather crafts home industry. If viewed from the point of functional theory, that is when it is said that basically everything (objects, animals) has the principle of function, use or benefit. In this case there is also a functional link between cultural elements in the social system of the local community. So it can be concluded that functional theory can be used as a knife of analysis in examining the existence home industry of the leather crafts. The implication of this research is that it can be used as a reference for further researchers to develop other objects of study when it is linked to elements of local wisdom.